2016
DOI: 10.3389/fendo.2016.00155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Social Stress and Maternal Intranasal Oxytocin and Vasopressin on Offspring Interferon-γ and Behavior

Abstract: Recent studies support the hypothesis that the adverse effects of early-life adversity and transgenerational stress on neural plasticity and behavior are mediated by inflammation. The objective of the present study was to investigate the immune and behavioral programing effects of intranasal (IN) vasopressin (AVP) and oxytocin (OXT) treatment of chronic social stress (CSS)-exposed F1 dams on F2 juvenile female offspring. It was hypothesized that maternal AVP and OXT treatment would have preventative effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The negative IFN-γ self grooming association suggests that this immune factor is generally involved in the regulation of self grooming with low IFN-γ values being associated with high levels of self grooming. Previous CSS studies have not found significant associations between IFN-γ and behavior in female F2 juveniles [ 20 ], and one explanation is that IFN-γ’s effects are more involved in overall neuronal development than the modulation of specific behaviors, and/or that downstream growth or immune factors are more critical to the expression of social behaviors. Previous studies of IFN-γ and social stress indicate that it is elevated in aggressive male mice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative IFN-γ self grooming association suggests that this immune factor is generally involved in the regulation of self grooming with low IFN-γ values being associated with high levels of self grooming. Previous CSS studies have not found significant associations between IFN-γ and behavior in female F2 juveniles [ 20 ], and one explanation is that IFN-γ’s effects are more involved in overall neuronal development than the modulation of specific behaviors, and/or that downstream growth or immune factors are more critical to the expression of social behaviors. Previous studies of IFN-γ and social stress indicate that it is elevated in aggressive male mice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…F2 juveniles and adults exhibit deficits in social behavior [ 17 , 18 ], and F2 dams display pervasive deficits in maternal care throughout lactation [ 19 ]. We have also established that intranasal vasopressin and oxytocin treatments in maternal rats, hormones critically involved in the regulation of social behavior and the stress response, can alter basal interferon-γ levels and social behavior in offspring [ 20 ]. Several reports have postulated that proinflammatory cytokines can impair behavior by increasing neuroplasticity in the reward pathway through direct interactions as well as indirectly by modulating neural growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies, such as optogenetics, are allowing more specificity in neural circuitry but are currently limited to comparatively simple behaviors or components of behavioral patterns. There is increasing evidence that the OT–VP receptor pathway is epigenetically tuned by experience, including gonadal hormones, stressors, and probably peptides as well ( 10 , 11 , 13 , 14 , 75 ). Although not reviewed here, processes such as methylation may be of particular relevance to explaining the role of context and experience in the regulation of social behavior.…”
Section: Interactive Functions Of Ot and Vpmentioning
confidence: 99%
“…The receptor variation characteristic of this system, and especially of VP has been associated with species and individual variation in behavior and brain function. Although sometimes overlooked in behavioral research, both peptides can have regulatory effects throughout the entire body, including the autonomic nervous system ( 42 ) and the immune system ( 53 , 73 75 ) with effects on inflammation and healing.…”
Section: Introductionmentioning
confidence: 99%
“…This anticancer effect is also associated with the immune regulatory functions of OXT. Intranasal OXT application to F1 rat dams was reported to increase serum interferon-γ level in F2 juvenile female offspring (Murgatroyd et al, 2016), which is associated with apoptosis of small-cell lung cancer (Zhou et al, 2006). It was also reported that peripheral use of OXT reduced stress-induced visceral hypersensitivity and activation of enteric glial reactivity (Xu et al, 2018), thereby increasing the defense of GI tract to inflammatory challenges.…”
Section: General Anticancer Effect Of Oxt and Its Approachesmentioning
confidence: 99%